Laparoscopic Versus Open Liver Resection for Colorectal Liver Metastases: A Comprehensive Systematic Review and Meta-analysis - Xie, Si-Ming; Xiong, Jun-Jie; Liu, Xue-Ting; Chen, Hong-Yu; Iglesia-García, Daniel; Altaf, Kiran; Bharucha, Shameena; Huang, Wei; Nunes, Quentin M.; Szatmary, Peter; Liu, Xu-Bao (Scientific reports, 2017)
The effects of laparoscopic liver resection (LLR) and open liver resection (OLR) on oncological outcomes for colorectal cancer liver metastases (CCLM) remain inconclusive. Major databases were searched from January 1992 to October 2016. Effects of LLR vs OLR were determined. The primary endpoints were oncological outcomes. In total, 32 eligible non-randomized studies with 4697 patients (LLR: 1809, OLR: 2888) were analyzed. There were higher rates of clear surgical margins (OR: 1.64, 95%CI: 1.32 to 2.05, p < 0.00001) in the LLR group, without significant differences in disease recurrence, 3- or 5-year overall survival(OS) and disease free survival(DFS) between the two approaches. LLR was associated with less intraoperative blood loss (WMD: −147.46 [−195.78 to −99.15] mL, P < 0.00001) and fewer blood transfusions (OR: 0.41 [0.30–0.58], P < 0.00001), but with longer operation time (WMD:14.44 [1.01 to 27.88] min , P < 0.00001) compared to OLR. Less overall morbidity (OR: 0.64 [0.55 to 0.75], p < 0.00001) and shorter postoperative hospital stay (WMD: −2.36 [−3.06 to −1.66] d, p < 0.00001) were observed for patients undergoing LLR, while there was no statistical difference in mortality. LLR appears to be a safe and feasible alternative to OLR in the treatment of CCLM in selected patients.